Hubungan Mobilisasi Dini Terhadap Penurunan Tinggi Fundus Uteri Ibu Nifas Di Bidan Praktek Mandiri (BPM) Susiyanti Tahun 2022 - Susiyanti Susiyanti; Ninsah Mandala Putri Sembiring (Jurnal Sains dan Kesehatan, 2022)
The postpartum period (puerperium) is the period after the release of the placenta until the reproductive organs recover as before pregnancy and normally the postpartum period lasts for 6 weeks or 40 days. . This study aims to determine the relationship between early mobilization and decreased uterine fundal height for postpartum women at BPM Susiyanti in 2022. This type of research is an analytic survey with a cross sectional approach. The number of samples used was 32 people. The data analysis technique uses the Chi Square test. the results obtained from 32 respondents, there is a relationship between early mobilization and acceleration of fundal height reduction in post partum mothers on the first and second days at the Independent Practice Midwife (BPM) Susiyanti.